The Role of Religious Tourism in the Ampel Region in Maintaining the Culture of Pilgrimage of the Wali's Tomb - Kusumaningtyas, Menur (MALIA: Jurnal Ekonomi Islam, 2023)
Pilgrimage to the tombs of saints is considered important for some Muslims. The tombs of saints in Java Island have now become tourist destinations to preserve cultural heritage and religious-based tourism, including the tomb of Sunan Ampel in Surabaya. This article aims to examine the content of the text through a qualitative and interdisciplinary approach, explaining the dimensions and strategies for developing pilgrimage tourism at the tomb of Sunan Ampel. The research results show that there are various types of sacred places, such as the tombs of the Wali Sanga, tombs of religious figures, and mosques left by the saints. Pilgrimage tourism at the tomb of Sunan Ampel has spiritual, social, cultural, and environmental components that require comprehensive planning and design, as well as a specific perspective to develop the tomb site, including the arrangement of food and souvenir sales areas, the conditions of the local community, cultural and social contexts, pilgrimage rituals and traditions, the needs of pilgrims, functional infrastructure, tourism, and services.